From Childhood to Power: The Formative Years of Jung Bahadur Rana - Rana, Saroj Pratap (HISAN: Journal of History Association of Nepal, 2025)
This study explores the formative years of Jung Bahadur Rana, tracing how ancestral legacy, personal adversity, and strategic action shaped his rise in nineteenth-century Nepal. It emphasizes Bal Narsingh Kunwar’s court access as crucial to Jung Bahadur’s early positioning, starting with the Kunwar family’s martial and administrative heritage. The contested narratives of his birthplace, such as Borlang, Mathura Benshi, or Thapathali, are examined as indicators of elite identity and historical legitimacy. After the Thapa faction fell, the study traces his fall into poverty and makes the case that these adversities strengthened his resolve and political instincts. His re entry into Kathmandu’s court politics, marked by bravery and tactical alliances, laid the groundwork for his ascent. Drawing on Erik Erikson’s Psychosocial Development Theory, the paper argues that Jung Bahadur’s childhood experiences were not incidental but foundational to the emergence of the Rana regime and the shaping of Nepal’s modern political history.